Effect of Cyclic Freezing-Thawing on the Shear Mechanical Characteristics of Nonpersistent Joints - Daxing Lei; Hang Lin; Yifan Chen; Rihong Cao; Zhijie Wen (Advances in Materials Science and Engineering)
The effects of freezing-thawing cycles and persistency differences have a significant impact on the shear mechanical properties of joints. In this paper, a series of joints direct shear tests were performed on freezing-thawing treated joints to investigate the effect of freezing-thawing cycles and the persistency on the shear strength deterioration of joints. Shear strength and residual strength decrease with the freezing-thawing cycle increase and joint persistency increase. Shear strength damage mainly generates in the initial stage of the freezing-thawing cycle, and the shear strength decreases slightly in the late freezing-thawing cycle stage. The freeze-thaw cycle has a minimal effect on the shear strength of joints with low persistency, yet has a great effect on joints with high persistency. The damage of joint roughness caused by freezing-thawing cycles increases with joint persistency increases. When the joint persistency is constant, the shear strength parameter decreases with the freezing-thawing cycle at first and then tends to be stable. Cohesion is the dominant factor that controls shear strength. When freezing-thawing cycles are constant, the friction angle decreases slowly with persistency at first and then decreases rapidly, and the friction angle is the dominant factor that controls shear strength.